Efficacy and safety of low-dose X-rays based intraoperative radiotherapy for high-grade gliomas: a single-center retrospective study - Wen, Zhongcheng; Liu, Jun; Bai, Yang; Zhou, Minghao; He, Jiajie; Xu, Ying; Yan, Ying; Li, Fuyong; Gong, Shun; Li, Jianan; Cao, Peng (Frontiers in Oncology, 2025)
BackgroundIntraoperative radiotherapy (IORT) is an emerging local therapy in the surgery of intra-axial brain tumors to improve clinical outcomes and accelerate the adjuvant oncologic therapy. Despite its use in neuro-oncology, the data regarding the role of IORT in the treatment of high-grade gliomas (HGGs) is sparse. Here we reported our single-institutional evidence concerning the efficacy and safety of IORT in the management of HGGs.MethodsA total of thirty patients diagnosed with HGGs who underwent surgical treatment and IORT at our center between October 2021 and October 2023 were included. Clinical data were collected and analyzed, including surgical parameters such as the gross total resection (GTR) rate, follow-up assessments of treatment responses (Karnofsky Performance Status [KPS] scores), treatment-related complications, overall survival (OS), and subsequent therapeutic interventions. Multivariable Cox regression analyses were performed to identify independent risk factors for survival in patients with HGGs.ResultsThe median IORT dose was 12 Gy prescribed to the applicator surface using the INTRABEAM system. The median OS was 11.0 months (IQR: 7.8–14.3), with a 1-year survival rate of 46.7%. No severe radiation-related adverse events, such as cerebral radiation necrosis or wound-related complications, were recorded. Kaplan-Meier analyses showed that patients who received post-operative radiotherapy and chemotherapy after IORT had better clinical outcomes than those who did not. Multivariable regression analyses indicated post-operative radiotherapy was independently correlated with favorable clinical outcomes.ConclusionLow-dose X-rays based IORT at doses of 10-12 Gy is generally safe for HGGs. Future prospective large-scale studies are needed to further evaluate the efficacy and safety of IORT with escalating doses. Even with the use of IORT, post-operative radiotherapy is essential for improving clinical outcomes of HGGs. This study provides clinical data on IORT for HGGs, which may represent a promising therapeutic approach for managing this disease.